Does herpes zoster predispose to giant cell arteritis: a geo-epidemiologic study - Ing, Edsel B (Clin Ophthalmol, 2018)
PURPOSE: Giant cell arteritis (GCA) is the most common systemic vasculitis in the elderly and can cause irreversible blindness and aortitis. Varicella zoster (VZ), which is potentially preventable by vaccination, has been proposed as a possible immune trigger for GCA, but this is controversial. The incidence of GCA varies widely by country. If VZ virus contributes to the immunopathogenesis of GCA we hypothesized that nations with increased incidence of GCA would also have increased incidence of herpes zoster (HZ). We conducted an ecologic analysis to determine the relationship between the incidence of HZ and GCA in different countries. METHODS: A literature search for the incidence rates (IRs) of GCA and HZ from different countries was conducted. Correlation and linear regression was performed comparing the disease IR of each country for subjects 50 years of age or older. RESULTS: We found the IR for GCA and HZ from 14 countries. Comparing the IRs for GCA and HZ in 50-year-olds, the Pearson product-moment correlation (r) was −0.51, with linear regression coefficient (β) −2.92 (95% CI −5.41, −0.43; p=0.025) using robust standard errors. Comparing the IRs for GCA and HZ in 70-year-olds, r was −0.40, with β −1.78, which was not statistically significant (95% CI −4.10, 0.53; p=0.12). CONCLUSION: Although this geo-epidemiologic study has potential for aggregation and selection biases, there was no positive biologic gradient between the incidence of clinically evident HZ and GCA.